STUDY OF INFORMATION AND COMMUNICATION TECHNOLOGY ASSET INVENTORY IN GOVERNMENT INSTITUTION (Empirical Study in Ministry of Communication and Information Technology) - nfn Kautsarina (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
Demands for the establishment of good governance, accountability and transparency prompted the government for constantly making improvements and changes to create good governance, with the development of e-government. As a facilitator e-governmen’ success key, ICT assets would have to be managed effectively in order to be utilized optimally. Therefore, it is deemed necessary to conduct asset inventory study of ICT in the Ministry of Communications and Information Technology. The study was conducted quantitatively through a survey of person in charge in IT at 64 work units. The finding indicate that conditions in the dimension of ICT is still weak in policies, institutions and risks. As a recommendation, it takes the policy, strategy and leadership commitment to optimize ICT assets from the planning stage to the stage of extermination.Keywords: asset, e-government, inventory, ICT